Species composition of the diatom communities in the watercourses of Northeastern Kamchatka with comments on abundant taxa and description of Gomphonema lepskayae sp. nov. - Mironov, Andrei; Glushchenko, Anton; Kezlya, Elena; Kulikovskiy, Maxim (Phytotaxa, 2025)
In this study, we investigate the diversity of diatom communities in several watercourses located in the Karaginsky district, Northeastern Kamchatka, Russia. The studied waterbodies are characterized by a wide range of ecological conditions in terms of pH level, electrical conductivity and solute concentration. Our analysis indicates the richness of diatom communities in the studied area. Hereby, we illustrate 24 most abundant diatom species from the analyzed waterbodies. Light microscopy-based morphological diagnoses are presented for all taxa. Notes on the distribution of the abundant diatom taxa and their ecological characteristics are provided. In addition, a new species—Gomphonema lepskayae sp. nov.—is described based on the results of light and scanning electron microscopy. The new species is distinguished from related taxa by valve symmetry, striae arrangement, morphology of axial and central areas and structure of the isolated pore.